Both epicardial and peri-aortic adipose tissue blunt heart rate recovery beyond body fat mass - Chang, Sheng-Hsiung; Chu, Po-Hua; Tsai, Cheng-Ting; Kuo, Jen-Yuan; Tsai, Jui-Peng; Hung, Ta-Chuan; Hou, Charles Jia-Yin; Lai, Yau-Hui; Liu, Chia-Yuan; Huang, Wei-Ming; Yun, Chun-Ho; Yeh, Hung-I; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Epicardial adipose tissue (EAT) as a marker of metabolic disorders has been shown to be closely associated with a variety of unfavorable cardiovascular events and cardiac arrhythmias. Data on regional-specific visceral adiposity outside the heart and its modulation on autonomic dysfunction, particularly heart rate recovery after exercise, remain obscure. Methods We studied 156 consecutive subjects (mean age: 49.3 ± 8.0 years) who underwent annual health surveys and completed treadmill tests. Multi-detector computed tomography-based visceral adiposity, including EAT and peri-aortic fat (PAF) tissue, was quantified using dedicated software (Aquarius 3D Workstation, TeraRecon, San Mateo, CA, USA). We further correlated EAT and PAF with blood pressure and heart rate (HR) recovery information from an exercise treadmill test. Metabolic abnormalities were scored by anthropometrics in combination with biochemical data. Results Increased EAT and PAF were both associated with a smaller reduction in systolic blood pressure during the hyperventilation stage before exercise compared to supine status (β-coefficient (coef.): −0.19 and −0.23, respectively, both p < 0.05). Both visceral adipose tissue mediated an inverted relationship with heart rate recovery at 3 (EAT: β-coef.: −0.3; PAF: β-coef.: −0.36) and 6 min (EAT: β-coef.: −0.32; PAF: β-coef.: −0.34) after peak exercise, even after adjusting for baseline clinical variables and body fat composition (all p < 0.05). Conclusion Excessive visceral adiposity, whether proximal or distal to the heart, may modulate the autonomic response by lowering the rate of HR recovery from exercise after accounting for clinical metabolic index. Cardiac autonomic dysfunction may partly explain the increase in cardiovascular morbidity and mortality related to both visceral fats.